A glimpse of the Nitrogen-Fixing Wheat possibility - Lee James Watson; Tara Puri Ducha Rahmani (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2022)
As the world's population grows at an exponential rate, greater food production becomes a requirement. Intensive agricultural methods, which are now used to produce the bulk of food, are unsustainable and will be unable to supply demand when natural resources become scarce. The industry faces a significant nitrogen demand, which must be met in order to combat hunger in emerging countries. This study used a literature review technique to investigate the potential for improved wheat crop yield through nitrogen fixation. It has been demonstrated that utilizing microorganisms such as cyanobacteria as biofertilizers or phytopathogen antagonists can boost the development and productivity of non-leguminous agricultural crops. Finally, the possible end result outweighs the costs. It's impossible to argue against the development of nitrogen-fixing wheat at this point in the technology's development. Whether it is possible to develop crops that rely solely on dinitrogen as a nitrogen source, or if the result is only a slight boost in wheat yields, the need to improve global food production needs research like the one described in this article.©2022 JNSMR UIN Walisongo. All rights reserved.